Is Covid-19 Sibling of SARS and MERS? A Review on: Novel Covid-19 - Devi, Savita; Singh, Kamaldeep (Indian Journal of Pharmaceutical Education and Research, 2020)
Pandemic times: Contemporary public health catastrophe terrifying the world over with the rapidly spreading of 2019-nCoV or SARS-CoV-2. Coronaviruses have pass over the species barriers to cause fatal disease in human since the 2002 and 2012; Severe Acute Respiratory Syndrome and Middle East Respiratory Syndrome respectively. It was suggested that SARS-CoV and SARS-CoV-2 are firmly related to each and hypothesized it originated in animal (bats) and was transmitted to humans. Though Novel Covid-19’s intermediary animal is not clear. As a matter of fact, transmission of Covid-19 is direct contact with infected people or inhalation of droplets thus; escalate its spread. World Health Organization stated the novel SARS-CoV-2 is one of the epidemic disease on January 30, 2020 and on March 11, 2020 declared a pandemic the rapidly spreading SARS-CoV-2- a globe first for corona virus. Additionally, the incubation phase is from 2 to 14 days. Usually the sign and symptoms are high temperature, dry cough, tiredness, sore throat, difficulty breathing (severe cases) AND malaise among others. The diagnosis can be done with Real Time Polymerase Chain Reaction test to suspected SARS-CoV-2 infection along with chest X-ray. Till time, no medicine or vaccines are prepared that can approved against SARS-CoV-2 or any human-infecting corona viruses. But some researchers have confirmed to curtail its effects by administrating antiviral drugs such as Oseltamivir, Ribavirin, Ganciclovir, Lopinavir AND Ritonavir.
Keywords: SARS-CoV-2; Corona virus; Epidemic; Pandemic; PCR